DETERMINING OF FREIGHT FORWARDER SERVICES USING DECISION ANALYSIS IN PT HDM - Qadri, Muhammad
PT HDM is a family-owned company established in 2012 that provides various laboratory needs. PT HDM sells many imported products due to the limited number of domestic manufacturers that provide the necessary laboratory equipment and chemicals clients require. PT HDM relies on imported products to meet the needs and demands of its customers, who come from the pharmaceutical industry, food sector, educational institutions, and research institutions. This makes the import process very important for PT HDM. In addition to handling imports in-house, PT HDM also utilizes the services of Freight Forwarders (PFFs) to assist in the import process.